Improved Electrochemical Performance of Surface Coated LiNi0.80Co0.15Al0.05O2 With Polypyrrole - Chen, Zhaoyong; Cao, Kaifeng; Zhu, Huali; Gong, Xiaolong; Liu, Qiming; Duan, Junfei; Li, Lingjun (Frontiers in Chemistry, 2019)
Nickel-rich ternary layered oxide (LiNi0.80Co0.15Al0.05O2, LNCA) cathodes are favored in many fields such as electric vehicles due to its high specific capacity, low cost and stable structure. However, LNCA cathode material still has the disadvantages of low initial coulombic efficiency, rate capability and poor cycle performance, which greatly restricts its commercial application. To overcome this barrier, a polypyrrole (PPy) layer with high electrical conductivity is designed to coat on the surface of LNCA cathode material. PPy coating layer on the surface of LNCA successfully is realized by means of liquid-phase chemical oxidation polymerization method, and which has been verified by the scanning electron microscopy (SEM), transmission electron microscope (TEM) and fourier transform infrared spectroscopy (FTIR). PPy-coated LNCA (PL-2) exhibits satisfactory electrochemical performances including high reversible capacity and excellent rate capability. Furthermore, the capability is superior to pristine LNCA. So, it provides a new structure of conductive polymer modified cathode materials with good property through a mild modification method.